Cultivar de soja "Juparanã" (UFV-7): comportamento no Estado do Espírito Santo - Sediyama, Carlos S; Sediyama, Tuneo; S Reis , Múcio; Lopes Gomes , José Luiz; Caetano , Laercio Francisco; Pereira , Messias G (Revista Ceres, 2025)
'Juparaná' or ‘UFV-T' is a new late maturing cultivar for central Brazil and is being recommended for planting in the State of Espírito Santo. It originated from the cross (‘Hardee’ x ‘IAC-2') X ‘UFV-1' and was initially tested as VX31-S-48, and later as UFV 80-68.